Korelasi Antara Durasi Penggunaan Komputer dengan Kejadian Astenopia pada Mahasiswa FST Universitas Pattimura - Ciputra, Dmytrick; Manery, Dodikrisno E; Embisa, Yushar A; Assagaf, Abdur Rahman; Ukratalo, Abdul M (Pusat Riset dan Inovasi Nasional, 2025)
According to the Indonesian Internet Service Providers Association (APJII) in 2018, approximately 49.52% of all internet users in Indonesia are aged between 19 and 34 years, with the majority of this age group being students. Prolonged computer use can lead to higher levels of asthenopia compared to other types of work. This study aims to examine the correlation between computer usage duration and the occurrence of asthenopia among students. A correlational design with a cross-sectional approach was employed in this study. A total of 76 participants were included, and data were collected via a questionnaire distributed online using Google Forms, which the respondents completed. The collected data were then analyzed univariately and bivariately using SPSS software. The results indicate that the majority of respondents experienced mild asthenopia, with a percentage of 78.9%. Statistical analysis showed no significant relationship between gender, duration of computer use, eye break intervals, history of major eye diseases, and medication consumption with the occurrence of asthenopia (p>0.05). However, a significant relationship was found between age and the occurrence of asthenopia (p<0.05).